Utilizing Real-Time Image Processing for Monitoring Bacterial Cellulose Formation During Fermentation - Darmawan Ari Nugroho; Lilik Sutiarso; Endang Sutriswati Rahayu; Rudiati Evi Masithoh (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
In general, nata is a bacterial cellulose results from bacterial fermentation of Gluconacetobacter xylinus. During the fermentation process, bacterial cellulose accumulates on the surface of the medium and is eventually visible. The parameter of the end of the fermentation process is indicated by the formation of bacterial cellulose sheets with a certain thickness. During this time, the determination of the success of the fermentation process is done by direct observation of the thickness formed. In this way, the failure of the fermentation process cannot be detected early. Real-time monitoring during the fermentation period will be very helpful to monitor the speed of bacterial cellulose formation and early failure detection of the fermentation process. Currently, image processing has been widely used for various purposes. This study describes how to utilize image processing to monitor bacterial cellulose formation during the fermentation process. For this reason, it is necessary to modify the fermentor by making an area to shoot and follow any thickness increase in the bacterial cellulose, as well as painting the fermentor in dark color to better contrast with the bacterial cellulose color. The device used is the Raspberry Pi, which has been connected to a web camera. Once the image has been captured, it is then processed to calculate the thickness, after which the thickness data are sent to the database.